SEXUAL BEHAVIOR AT RISK OF SEXUALLY TRANSMITTED INFECTIONS IN PRISON: A DESCRIPTIVE STUDY AT SEMARANG CLASS I PENITENTIARY - Nur Wulan Nugrahani; Arie Udijono; Lintang Dian Saraswati; Arie Wuryanto (Journal of Public Health for Tropical and Coastal Region, 2020)
High-risk behavior placed inmates to be one of certain population to be vulnerable to sexually-transmitted infections (STI) due to the discontinuity of sexual needs in imprisonment. The purpose of this study is to describe the history of STIs-risked sexual behavior of inmates before and during imprisonment. This research was an observational study with a cross sectional study design. The samples were 100 male inmates in Semarang Class I Penitentiary. Univariate data analyzed and presented in frequency distribution. Characteristics of respondents in this study include the majority of respondents aged less than 40 years (70%), completed high school (42%), and married (48%). Sexual orientation before and during imprisonment were all heterosexual (100%). Historical description of STIs-risked sexual behavior with a high risk category were 53%, while during imprisonment were 71%. Based on sexual behavior in prison, 54% doing masturbation involving genital stimulation and pornography, 13% touching intimate parts in the visiting room, 5% had intercourse with the opposite sex in prisons. This findings implied that the sexual needs of inmates in prison are real and need to be channeled in a healthy manner.